Using hand painting in the fabrication of a negative refractive index metamaterial based on circular shape with paper as the dielectric - Hamonangan M , Felix R.M. Hamonangan M; Yudistira , Hadi Teguh Yudistira; Qalbina , Fitrah; Saputro , • Adhitya Gandaryus; Faisal , Amir (Green and Sustainable Materials Society, 2024)
This study aims to use the hand-painting method in designing and fabricating a metamaterial based on a circular shape that exhibits a negative refractive index over the microwave spectrum. Hand painting is a simple and inexpensive fabrication method. This study applies silver ink as a periodic conductor to glossy paper as the dielectric substrate. The spectrum of investigation in this study is 3–6 GHz, and the experiment results are compared with the simulation results. The slight error obtained between transmission results from the simulation and the experiments reflects limitations in the fabrication methods used. Overall, the experiment results have a similar trend to the simulation results. The electrical properties of the metamaterial are retrieved from the transmission and reflection simulation results. The simulation results are employed instead of the experimental results because of the fluctuating data provided by the latter. The refractive index presents a negative value at 3–3.6 GHz.